A response to iron involving carbon metabolism in the opportunistic fungal pathogen Candida albicans - Ritu Garg; Zhengkai Zhu; Francisco G. Hernandez; Yiran Wang; Marika S. David; Vincent M. Bruno; Valeria C. Culotta (mSphere)
ABSTRACT Iron (Fe) is an essential micronutrient, and during infection, the host attempts to starve pathogens of this vital element through a process known as nutritional immunity. Successful pathogens have evolved means to evade this attack, an example being Candida albicans, the most prevalent human fungal pathogen. When Fe-starved, C. albicans induces multiple pathways for Fe uptake using the SEF1 trans-regulator, and we now describe a previously unrecognized effect of Fe on C. albicans metabolism that occurs independent of SEF1. Specifically, Fe limitation leads to inhibition of pyruvate dehydrogenase (PDH) connecting glycolysis to mitochondrial respiration. PDH inactivation involves loss of the LAT1 catalytic subunit harboring a lipoic acid co-factor. Protein lipoylation is a Fe-S dependent process, and lipoylated alpha-ketoglutarate dehydrogenase is also inhibited in Fe-starved C. albicans. SEF1 does not protect against PDH inactivation, and despite SEF1 induction of Fe import genes, cellular Fe levels drop dramatically during chronic Fe starvation. Such loss of LAT1 and lipoylation is also seen in Fe-starved bakers’ yeast Saccharomyces cerevisiae. In both yeast species, glucose is diverted toward the pentose phosphate pathway (PPP) and PPP production of NADPH is increased in response to low Fe and PDH loss. Additionally, glucose consumption is lowered in Fe-starved C. albicans, and non-PDH alternatives to producing Ac-CoA are induced, including pyruvate bypass and fatty acid oxidation pathways. C. albicans can adapt well to the effects of micronutrient loss on cell metabolism.IMPORTANCEWe describe a new response to Fe-starvation in a fungal pathogen involving carbon metabolism. Pyruvate dehydrogenase (PDH) that is central to glucose metabolism is inactivated at the post-translational level in Fe-starved cells. Nevertheless, the fungal pathogen can thrive by activating backup systems for metabolizing glucose. Methods that inhibit these compensatory pathways for carbon metabolism may prove beneficial in future anti-fungal strategies.